2020
DOI: 10.1249/mss.0000000000002465
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow Restriction Training Blunts Chronic Kidney Disease Progression in Humans

Abstract: Purpose This study aimed to verify the effect of 6 months of periodized resistance training (RT) with and without blood flow restriction (BFR) in patients with stage 2 chronic kidney disease (CKD) on glomerular filtration rate (GFR), uremic parameters, cytokines, and klotho–fibroblast growth factor 23 (FGF23) axis. Methods A total of 105 subjects were randomized in three groups of 35 each: control (CTL), RT, and RT + BFR. A first visit was required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 39 publications
0
63
0
1
Order By: Relevance
“…In addition, exercise also helps in the treatment of kidney-related diseases. Resistance training for patients with stage II chronic kidney disease can improve uremia parameters and the klothof-FGF23 signaling pathway, thereby alleviating the progression of the disease ( Corrêa et al, 2021 ) ( Figure 3 ).…”
Section: The Effect Of Mechanical Stimulation On Bone-derived Secreted Proteinmentioning
confidence: 99%
“…In addition, exercise also helps in the treatment of kidney-related diseases. Resistance training for patients with stage II chronic kidney disease can improve uremia parameters and the klothof-FGF23 signaling pathway, thereby alleviating the progression of the disease ( Corrêa et al, 2021 ) ( Figure 3 ).…”
Section: The Effect Of Mechanical Stimulation On Bone-derived Secreted Proteinmentioning
confidence: 99%
“…In humans with chronic kidney disease, an attenuation of proinflammatory markers blunting the progression of this disease was observed [32]. This attenuation might be associated with a decrease in inflammation and macrophage infiltration in the kidney, attenuating renal fibrosis, as demonstrated in rodents.…”
Section: Discussionmentioning
confidence: 88%
“…The presented arguments are results from a relay on the available literature with speculative character. Even so, robust evidence demonstrated that RT has potent antioxidant, anti-inflammatory effects and a positive impact on the metabolism profile and muscle strength [ 12 , 14 , 28 ], which may contribute to BDNF levels enhancement, mental health, and quality of life of patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…This study is part of a large trial registered on the Brazilian clinical trials registration: Available online: , accessed on 28 July 2021, no. RBR-3gpg5w and also registered in the World Health Organization international clinical trial registry platform: Available online: , no U1111-1237-8231 (30 July 2019) [ 12 , 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation